The protective effect of vitamins (C, E), selenium, silymarin and Rehydran-N against lead toxicity under heat stress conditions on some blood parameters on male rats - Shalan, M.J; Dh, Abd Ali W.; Ibrahim, Selim S.; Fouad, Ibrahim (Al-Mukhtar Journal of Sciences, 2008)
This study aimed to investigate using vitamins C, E, Selenium, and rehydration solution on reducing lead toxicity under heat stress conditions. male albino rats were subdivided into four groups: the first was a control group, the second was exposed to heat stress (40 ± 2 oC) in a closed chamber, the third received 25 mg/100 g body weight lead acetate and exposed to the same heat stress conditions, the forth was supplemented with1 mg/100 g body weight of each of vitamins C, E, Silymarin and 0.01mg/100 gm of B.W selenium and drank rehydran solution . Blood samples were collected after 25 days of treatment. Lead induced significant elevations in blood glucose, total protein, cholesterol, lead, Treatment of rats with vitamins C, E, silymarin, selenium and rehydran–n resulted in marked improvement of most parameters under investigation.